Critically Ill Recipients of Weight-Based Fluconazole Meeting Drug-Induced Liver Injury Network Criteria. (December 2019) - Joseph, Merlyn; Brady, Rebecca; Attridge, Russell; Cota, Jason; Horlen, Cheryl; Lusk, Kathleen; Attridge, Rebecca L.
Background: Fluconazole-associated liver injury is estimated to occur in <10% of patients; however, effect of weight-based fluconazole dosing on liver injury is unknown. Furthermore, no studies have systematically applied the Drug-Induced Liver Injury Network (DILIN) Criteria to identify patients who may have drug-induced liver injury in an intensive care unit (ICU) setting.Objective: This study evaluated how often patients met DILIN criteria when receiving fluconazole daily doses of <6 mg/kg versus ⩾6 mg/kg.Methods : This dual-center, retrospective cohort study was performed in hospitalized critically ill fluconazole recipients. We compared liver function tests (LFTs) upon fluconazole initiation to peak LFTs within 2 weeks after discontinuation using DILIN criteria. The primary objective was to evaluate the number of patients meeting DILIN criteria when receiving fluconazole daily doses of <6 mg/kg versus ⩾6 mg/kg. Secondary objectives were to evaluate incidence of patients meeting DILIN criteria in patients with renal dysfunction, cirrhosis, septic shock, or those receiving a loading dose.Results : Of 248 patients included, 90% had a documented fungal infection or received empiric therapy for suspected invasive candidiasis. In patients receiving <6 mg/kg of fluconazole, 55% (110/199) met DILIN criteria versus 46.9% (23/49) in the ⩾6 mg/kg cohort ( P = .20). Only 14.5% of patients meeting DILIN criteria also met the definition for hepatocellular damage. Weight-based fluconazole dose and creatinine clearance <50 mL/min were not independent risk factors for meeting DILIN criteria. However, 77.3% of patients with cirrhosis met DILIN criteria (OR 4.84 [95% confidence interval, CI, 2.61-9.28]) and 76.3% with septic shock met DILIN criteria (OR 4.56 [95% CI, 2.44-8.88]).Conclusion : Weight-based fluconazole dosing did not affect the number of critically ill recipients who met DILIN criteria. However, DILIN criteria may overestimate the incidence of fluconazole-associated liver injury in critically ill patients.